Successful treatment of a patient with middle aortic syndrome and renovisceral involvement using aorto-aortic bypass: case report and review of recent literature - Meyer, Alexander; Kuefner, Michael A.; Schmid, Andrea; Heinz, Marco; Lang, Werner (Annals of Vascular Surgery, 2014)
Middle aortic syndrome (MAS), defined as localized abdominal or thoracic aortic hypoplasia, represents an extraordinary rare condition, often diagnosed in younger patients with severe renal hypertension. Etiology is divided into congenital and acquired causes (e.g., Takayasu disease). Because of its extremely unfavorable course, treatment of symptomatic patients is mandatory, whereas open surgery with aorto-aortic bypass or patch aortoplasty is considered the standard therapy. This report describes a case of a 19-year-old Macedonian woman presenting with MAS and renal hypertension who was successfully treated with aorto-aortic bypass, including reconstruction of both renal and the hepatic and superior mesenteric arteries, and reviews the current literature.
EVALuna2:14342